AN ANALYSIS ON THE SECOND SEMESTER STUDENTS’ ABILITY IN PRONOUNCING TONGUE TWISTER AT THE ENGLISH EDUCATION DEPARTMENT OF STKIP INSAN MADANI AIRMOLEK - Guspa Ria; M. Sabri; Loly Novita (INOVISH JOURNAL, 2021)
This research uses descriptive method which tries to find out the students’ ability in pronouncing tongue twister. The data for the research were gathered by delivering a kind of oral test which required the second semester students to pronounce the sentences in tongue twister at the English Education Department of STKIP Insan Madani Airmolek.  When the data have been analised for the research finding, the authors concluded that the students’ability in pronouncing tongue twister is considered less because they have limited knowledge and less practice. The findings of the research are then expected to give some points of view for lecturers, escpecially those who teach Pronunciation to have various teaching techniques to get their students’ attention to learn and practice more about Pronunciation. The lecturers can also use interesting auido visual teaching media so that the students know how to pronounce words, phrases or sentences like native speakers do. Key Words: Pronunciation, Tongue Twister, Ability